Learning from the West, learning from the East: the emergence of the study of Buddhism in Japan and Europe before 1900 - Licha, Stephan; Krämer, Hans Martin (Studies on East Asian religions, 2023)
This volume offers a new perspective on the formation of academic Buddhist studies by giving equal weight to the agency of Asian and European actors. thus filling an important lacuna in critical scholarship on the history of Orientalist knowledge
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Geschichte 1850-1900; Forschung; Buddhismus; Europa; Japan